The Effects of position and sector on the employees’ job satisfaction: an application in telecomunication sector - Yücel, Pelin (My University, 2005)
Bu çalışmanın amacı, çalışanların iş tatmini farklılıklarını pozisyona (müdür olanlar ve müdür olmayanlar) ve sektöre göre (kamu sektörü ve özel sektör) incelemektir. Ayrıca, çalışanların iş tatmininin, cinsiyet, yaş, eğitim seviyesi gibi demografik değişkenlere göre değişip değişmediğine bakılmaktadır. Çalışanlar arasındaki iş tatmini farklılıkları, içsel iş tatmini ve dışsal iş tatmini olmak üzere iki boyutta incelenmiştir. Çalışmada, kamu sektörü ve özel sektörde faaliyet gösteren 3 farklı telekomünikasyon firmasında çalışan 112 kişiye Minnesota İş Tatmini Anketini’nin kısa formu uygulanmıştır. Firmalardan birisi, kamu sektöründen (Türk Telekom), diğer ikisi özel sektördendir (Ericsson T.A.Ş. ve Turkcell). Bu çalışmada iki ana hipotez test edilmiştir. H1: Müdür olarak sınıflandırılan çalışanlar çoğunlukla, işin kendisi ve başarı gibi içsel faktörlerden tatmin olurken; müdür olarak sınıflandırılmayan çalışanlar çoğunlukla, ücret ve çalışma koşulları gibi dışsal faktörlerden tatmin olmaktadır. H2: Özel sektör çalışanları, kamu sektörü çalışanlarından daha fazla işlerinden tatmin olmaktadırlar. Ayrıca, iş tatmini ile demografik değişkenler arasındaki ilişki incelenmiştir. Başka bir deyişle, çalışanların iş tatmini seviyelerinin cinsiyet, yaş ve eğitim seviyesi gibi demografik değişkenlere göre değişip değişmediğine bakılmıştır. Çalışmanın önemli bulguları şunlardır: Müdür olarak çalışan kişilerin, hem içsel hem de dışsal iş tatmini boyutları bakımdan, müdür olarak çalışmayan kişilere göre işlerinden daha fazla tatmin oldukları bulunmuştur. İlk hipotez yarı yarıya desteklenmiştir. Özel sektör çalışanlarının, içsel ve dışsal iş tatmini boyutları bakımından, kamu sektörü çalışanlarına göre işlerinden daha fazla tatmin oldukları bulunmuştur. İkinci hipotez desteklenmiştir. Cinsiyet, yaş ve medeni durumla ilgili olarak, çalışanlar arasında, ne içsel ne de dışsal iş tatmini boyutları bakımından anlamlı farklar bulunmamıştır. Eğitim seviyesine göre, çalışanlar arasında, içsel ve dışsal iş tatmini boyutları bakımından anlamlı farklar bulunmuştur. Üniversite mezunlarının, içsel iş tatmini boyutu bakımından, lise mezunlarından daha fazla işlerinden tatmin oldukları görülmüştür. Dışsal iş tatmini boyutu bakımından, hem üniversite hem de yüksek lisans ve doktora mezunlarının, ön lisans (yüksek okul) mezunlarından daha fazla işlerinden tatmin oldukları bulunmuştur. Çalışma süresine göre, dışsal iş tatmini boyutu bakımından, en yüksek kıdeme (17-28 yıl) sahip çalışanlarla orta seviyede kıdeme (6-8 yıl) sahip çalışanlar arasında anlamlı bir fark bulunmuştur. En yüksek kıdem seviyesine sahip çalışanların, orta kıdem seviyesine sahip çalışanlardan daha fazla işlerinden tatmin oldukları görülmüştür.

The objective of this study is to examine the differences in job satisfaction levels of employees according to position (managers and non-managers) and sector (public sector and private sector). In addition, it was investigated if the job satisfaction levels of employees changed with demographic variables such as gender, age, educational level or not. The differences of job satisfaction levels between employees was examined in two dimensions as intrinsic job satisfaction and extrinsic job satisfaction. In the study, the short form of Minnesota Satisfaction Questionnaire was conducted to 112 employees who work in three different telecomunication companies from the public and private sectors. One of the companies is from public sector (Türk Telekom), the other two are private sector (Ericsson T.A.Ş. and Turkcell). Two main hypothesis were tested in this study. H1: The employees classified as managers were mostly satisfied with intrinsic job factors such as the work itself and achievement, while the employees classified as non-managers were mostly satisfied with extrinsic job factors such as pay and working conditions. H2: The employees who work in the private sector were more satisfied with their jobs than the employees who work in the public sector within the telecomunication companies. In addition, it was investigated the relationship between the job satisfaction and demographic variables. In other words, it was examined if the job satisfaction levels of employees changed with the demographic variables such as gender, age and educational level or not. The important findings of the study are the following. It was found that the employees who work as managers were more satisfied with their jobs than the employees who work in as non-managers in relation to both intrinsic and extrinsic job satisfaction dimensions. H1 was partially supported. It was found that the employees working in the private sector were more satisfied with their jobs than the employees working in the public sector in relation to both intrinsic and extrinsic job satisfaction dimensions. H2 was supported. In relation to gender, age and marital status, significant differences were not found between the employees with respect to neither intrinsic nor extrinsic job satisfaction dimensions. In relation to educational level, significant differences were found between employees with respect to both intrinsic and extrinsic job satisfaction dimensions. University graduates were found to be more satisfied with their jobs than high school graduates in relation to intrinsic job satisfaction dimension. In relation to extrinsic job satisfaction dimension, both university graduates and master and doctorate graduates were found to be more satisfied with their jobs than pre-graduates. In relation to tenure, it was found a significant difference between the employees who had the highest level of seniority (17-28 years) and the employees who had middle level of seniority (6-8 years) with respect to extrinsic job satisfaction dimension. The employees who had the highest seniority levels were found to be more satisfied with their jobs than the employees who had middle seniority levels.
Keywords: İş Memnuniyeti; Personel Yönetimi; Verimlilik